2006
DOI: 10.1007/s10832-006-5410-9
|View full text |Cite
|
Sign up to set email alerts
|

Niobium doping effects and ferroelectric relaxor behavior of bismuth lantanium titanate

Abstract: Ferroelectrics Bi 3.25 La 0.75 (Ti 3−x Nb x )O 12 (BLTN, x = 0 ∼ 0.1) solid solution systems were prepared, and Nb doping effects and relaxor behaviors were investigated. The BLTN single phases were confirmed by XRD. The phase transition temperature decreased as the Nb content increased, and the corresponding dielectric constant maximum broadened. The temperature T m of the dielectric maximum depended on frequency and increased, which indicate that the relaxor behavior was caused by Nb substitution. The substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The peak in the real part of the dielectric constant of undoped CBN exhibits a smaller value of the full width at half maximum (FWHM) than the one for SBN. By comparison with the cerium doped sample it is evidenced that the doping induces a broadening of the peak in the dielectric constant which indicates a more diffuse phase transition characteristic of the material [10,15]. It can be concluded that the dopant has a strong influence on the characteristic of the ferroelectric phase transition of CBN.…”
Section: Resultsmentioning
confidence: 89%
“…The peak in the real part of the dielectric constant of undoped CBN exhibits a smaller value of the full width at half maximum (FWHM) than the one for SBN. By comparison with the cerium doped sample it is evidenced that the doping induces a broadening of the peak in the dielectric constant which indicates a more diffuse phase transition characteristic of the material [10,15]. It can be concluded that the dopant has a strong influence on the characteristic of the ferroelectric phase transition of CBN.…”
Section: Resultsmentioning
confidence: 89%
“…The temperature T m , corresponding to the maximum value of the dielectric constant, is shifted to higher temperature and the maximum value of the dielectric constant is decreased with increasing frequency. The observed diffuse phase transition and frequency dispersion of the dielectric constant in the BCT ceramic, characteristic of the relaxor ferroelectrics behavior, are not typical dielectric behavior of pure and La modified bismuth titanate ceramics [4,10,20]. Unlike in normal ferroelectric phase transitions whose permittivity above the Curie point should obey the Curie-Weiss law (e = C/(T À T CW )), where C is the Curie constant and T CW is the Curie-Weiss temperature, in relaxor ferroelectric materials this law is valid only at temperatures much higher than temperature of maximum relative dielectric constant T m (typically by hundreds of degrees) [21].…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 77%
“…5b. It is shown that this low-frequency dielectric dispersion at low temperature could be correlated with high concentration of defects such as bismuth and oxygen vacancies [4,16,19].…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%
See 2 more Smart Citations